Relación entre lateralidad y capacidad atencional en el desarrollo De los procesos lectores - Bustamante Parra, Andrea Catalina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article supports a reflection on the importance of neuropsychological processes such as laterality and attentional levels, to achieve a good learning and acquisition of reading. The mastery of reading is undoubtedly one of the most complex learning that occurs in the early school years as it requires a certain mental and physical maturity. The theoretical considerations were made from the perspectives of some authors related to the theme of the development of the reading processes was presented.